The Influence Of E-Service Quality And E-Trust On E-Loyalty Mediated By E-Satisfaction (Study On Shopee Application Users In South Jakarta) - Teuku Fadhil Magistra; Prima Mulyasari Agustini (Sean Institute, 2024)
This study aims to examine the effect of E-Service Quality and E-Trust on E-Loyalty among Shopee app users in South Jakarta, with E-Satisfaction as a mediating variable. The sample was obtained using probability sampling and consists of 104 respondents.Using a quantitative approach and SEM-PLS analysis, this study reveals interesting findings. The results show that both E-Service Quality and E-Trust have a significant and positive effect on E-Satisfaction among Shopee users. Furthermore, this study also proves that E-Satisfaction is a key factor in increasing E-Loyalty. E-Service Quality has been proven to directly and indirectly (through E-Satisfaction) influence E Loyalty. However, the results also show that E-Trust does not directly affect E-Loyalty when mediated by E-Satisfaction. This finding indicates that although trust is an important factor in building customer relationships, its influence on loyalty is more focused on increasing customer satisfaction first. Overall, this study makes a significant contribution to understanding the dynamics of the relationship between service quality, trust, satisfaction, and customer loyalty in the context of e-Commerce. The findings can be a reference for e-Commerce companies, especially Shopee, in formulating more effective strategies to increase customer loyalty. By focusing on improving service quality and building customer trust, companies can create a more satisfying shopping experience, which will ultimately increase customer loyalty.